Problems of Quality Assurance for Socio-Economic Data at Local Level - Ogay М. Yu. (Statistics of Ukraine, 2020)
The process of decentralization involves the enhanced interest of local power bodies in carrying out an effective benchmarking at local level, along with the increasing demand on relevant and reliable information on the development of territorial communities. Today, the local self-government faces financial and technical limitations in creating effective local systems for information support. It follows that the only way of producing a unified statistical support as a tool for performance analysis at local level is developing a centralized information system. The article contains an analysis of the quality of the existing centralized information system, which viability is supported by the Association of Ukrainian Cities. The computerized system of municipal statistics, developed in Ukraine, is an online system for collection, storage and processing of information on the core areas of life activities of territorial communities and self-government bodies. The system is based on the advanced principles of creation and operation of information products, whereas its organization, structure and technological tooling on the whole is compliant with analogous systems used in other spheres and in some other countries. However, most part of the indicators for which the data are collected and processed by the system does not comply with the core dimensions of quality, namely: relevance (topicality) / compliance with user needs; accuracy/reliability of estimated figures; timeliness and punctuality of production and publishing of processed data; accessibility and comprehensibility/clearness of metadata; comparability; consistency/coherence of indicators in space and time. The author’s study laid the basis for the elaborated recommendations on quality enhancement for the data collected at municipal level. A reliable information system must meet the following requirements: compliance of the system’s purpose and functions with user needs; coverage of the maximal number of administrative-territorial units; free access for users by hierarchical approach; availability of computerized data conversion; optimization of the set of primary, secondary and summary indicators and metadata that are developed by standard forms; use of advanced methods for data analysis and presentation given well-developed monitoring capabilities; viability and provision of appropriate professional support. If implemented, these recommendations will enable to form the solid information basis for comprehensive monitoring of life activities of cities and local communities in Ukraine.